Diagnosis of Papillon-Lefèvre syndrome: review of the literature and a case report - Adamski, Zygmunt; Burchardt, Dorota; Pawlaczyk-Kamieńska, Tamara; Borysewicz-Lewicka, Maria; Wyganowska-Świątkowska, Marzena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2020)
Papillon-Lefëvre syndrome (PLS), classified as ectodermal dysplasia, is an autosomal recessive condition related to the cathepsin C (CTSC) gene mutation. The first clinical symptoms, occurring most commonly between the ages of 1 and 4, are palmoplantar hyperkeratosis and also periodontitis resulting in the loss of most or all teeth in the same sequence in which they erupted. Most often the redness of palms and soles precede the occurrence of keratoderma. Moreover, excessive sweating, moderate mental retardation, the tendency to purulent skin and internal organs infection may occur. Lack of cathepsin seems to have a crucial role in the intensity of symptoms. In most of the patients, there can be observed impairment of phagocytosis and chemotaxis of neutrophils, granulocytes, leukocytes and cytotoxic lesion of fibroblasts and macrophages. Also, functional impairment of lymphocytes, neutrophils, and monocytes is observed. The study, using flow cytometry, showed a decreased percentage of T cells CD8+ and increased CD4:CD8 ratio.